Schminkpaletten mit zwei Köpfen: reale Vorbilder aus der Natur ? - Theis, Christoffer (Göttinger Miszellen, 2017)
The article presents some thoughts about the cosmetic palette New York, Metropolitan Museum of Art, Acc.-No. 10.176.78 and a new interpretation of the piece. It can be interpreted as a depiction of a two-headed turtle, a representation of a real-life